The impact of bruxism on orofacial health and performance in athletes - a systematic review - Różak, Patrycja; Nosowicz, Konstancja; Wójcik, Joanna; Musielińska, Marcelina; Malicka, Patrycja; Draguła, Michał (Journal of Education, Health and Sport, 2026)
Background Awake bruxism (AB), repetitive tooth clenching or grinding during wakefulness, is increasingly recognized in athletes, likely driven by competitive stress and high training loads. A PRISMA-based review of PubMed studies (2010-2024) included 23 studies, showing a pooled bruxism prevalence of ~34% in athletes, with rates up to 60-70% in elite sport, compared with ~23% in the general adult population. Psychological stress, performance pressure, and physical strain are key risk factors. AB is centrally mediated, involving dopaminergic and frontal-limbic pathways. Diagnosis relies mainly on self-report and clinical signs, with emerging use of ecological momentary assessment. Management is largely behavioral and interdisciplinary, including stress reduction, habit-reversal therapy, occlusal appliances, physiotherapy, and biofeedback. AB may negatively affect orofacial health and athletic performance, highlighting the need for greater awareness and standardized assessment. Materials and methods A PRISMA-based systematic PubMed search included studies from the past 15 years examining bruxism in athletic populations. Eligible studies comprised observational studies, clinical trials, and systematic reviews assessing awake and/or sleep bruxism in athletes. Results Both awake and sleep bruxism are frequently reported among athletes and are strongly associated with stress, competitive pressure, and high training loads. Most studies used self-reported and clinical assessments, while objective diagnostic methods were less common. Management was typically interdisciplinary, emphasizing behavioral strategies, stress control, and occlusal protection. Conclusion Bruxism is a multifactorial and clinically relevant condition in athletes that may affect orofacial health and performance. Early recognition, multidisciplinary management, and standardized diagnostic criteria are essential, and further high-quality research is needed.